Smart Aquaculture: Automated Fish Feeding with Blynk Alerts - Budi Wibowo; Nida Pristyan Ramadhani; Fachri Alfianza; Febriano Anggawa Rizky; Taufik Hidayat (Jurnal Komputer dan Elektro Sains, 2025)
Rapid developments in aquaculture have driven the need for efficient and sustainable feeding systems. This study presents the design and implementation of an automatic fish feeder using the Wokwi platform, integrated with the Blynk application. The system aims to deliver feed at optimal intervals and quantities, improving fish growth while minimizing waste. The research utilizes ESP32 as the main controller and servo motors to operate the feeder mechanism. Feeding schedules can be remotely controlled via the Blynk mobile app, allowing for flexible and precise feed management. Testing results indicate that the system consistently provides accurate feed portions at designated intervals, demonstrating reliability and ease of use. This automated feeder offers a cost-effective and environmentally friendly solution for aquaculture, reducing the labor and inefficiencies associated with manual feeding. Consequently, this innovation represents a significant advancement in aquaculture technology, promoting sustainable practices and enhancing overall operational efficiency.